2004
DOI: 10.1177/107424840400900i105
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fenofibrate on Serum Inflammatory Markers in Patients With High Triglyceride Values

Abstract: In addition to its well-known hypolipidemic effects, fenofibrate may also possess significant anti-inflammatory properties that can contribute its antiatherogenic effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
2
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 39 publications
(34 reference statements)
1
38
2
2
Order By: Relevance
“…Fibrates may also decrease plasma levels of inflammatory markers (e.g. CRP) that, in turn, influence MMP expression [279,280]. Based on these findings, it has been suggested that the fibrate-plus-statin combination could be a promising therapeutic strategy for diabetic atherosclerosis [281].…”
Section: Inhibition Of Metalloproteinases As Therapeutic Strategies Fmentioning
confidence: 99%
“…Fibrates may also decrease plasma levels of inflammatory markers (e.g. CRP) that, in turn, influence MMP expression [279,280]. Based on these findings, it has been suggested that the fibrate-plus-statin combination could be a promising therapeutic strategy for diabetic atherosclerosis [281].…”
Section: Inhibition Of Metalloproteinases As Therapeutic Strategies Fmentioning
confidence: 99%
“…Cerivastatin decreased serum CRP by 49.5% and fenofibrate by 29.8% (127). Micronized fenofibrate given daily in the dose of 200 mg to patients with hypertriglyceridemia reduced the serum levels of CRP by 34% (138). In a crossover study including otherwise healthy men with mixed dyslipidemia, the effects of fenofibrate, 200 mg daily, on CRP levels were compared with those of atorvastatin, 10 mg/daily for 10 weeks.…”
Section: Fenofibratementioning
confidence: 99%
“…Following lower extremity bypass operations, elevated CRP levels are associated with an increased risk of graft occlusion and postoperative e v e n t s 2 3-2 5 . I n p a t i e n t s u n d e r g o i n g c a r o t i d 40 , statins (atorvastatin [41][42][43][44] , rosuvastatin 35,41,42 , fluvastatin 45 and pravastatin 46 ), fenofibrate 43,44,47 and ciprofibrate 48,49 . The mechanisms by which these drugs lower CRP levels are more extensively reviewed elsewhere 50 .…”
mentioning
confidence: 99%